2021
DOI: 10.1186/s13075-021-02685-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in clinically suspect arthralgia: the role of power Doppler to predict rheumatoid arthritis development

Abstract: Objective To determine the usefulness of power Doppler (PD) ultrasound (US) to predict rheumatoid arthritis (RA) development in patients with clinically suspect arthralgia (CSA). Methods Retrospective analysis of a US unit cohort over a 1-year period. Patients with CSA and no previous diagnosis of inflammatory arthritis (IA) were included for analysis. All underwent bilateral US examination of the hands and/or feet according to the EULAR guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A major intrinsic limitation of our study is represented by the fact that most of the studies focused on the assessment of entheses, with limited information on the joints and no information on tenosynovitis. While in spondyloenthesoarthritis enthesitis has been identified as the primary lesion characterizing the disease process, tenosynovitis is emerging as a possible early lesion in new-onset peripheral inflammatory pain ( 36 ), and its low prevalence in healthy subjects suggests specificity for arthritis ( 37 ). In addition, tenosynovitis was the only lesion presenting with a different frequency in psoriatic patients with or without arthralgia ( 16 ), thus it might represent an interesting feature to assess also in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…A major intrinsic limitation of our study is represented by the fact that most of the studies focused on the assessment of entheses, with limited information on the joints and no information on tenosynovitis. While in spondyloenthesoarthritis enthesitis has been identified as the primary lesion characterizing the disease process, tenosynovitis is emerging as a possible early lesion in new-onset peripheral inflammatory pain ( 36 ), and its low prevalence in healthy subjects suggests specificity for arthritis ( 37 ). In addition, tenosynovitis was the only lesion presenting with a different frequency in psoriatic patients with or without arthralgia ( 16 ), thus it might represent an interesting feature to assess also in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of US tenosynovitis to predict IA has been less well studied than with MRI and has shown mixed results. Molina Collada et al found that in a cohort of CSA patients PD tenosynovitis at baseline was the only independent predictor of RA and IA development ( 32 ). In contrast van de Stadt et al did not find that US tenosynovitis was significantly predictive of IA progression at joint or patient level ( 29 ).…”
Section: Which Imaging Technique?mentioning
confidence: 99%
“…Musculoskeletal ultrasound (MSUS) at present time plays a crucial role in the diagnosis and treatment of the rheumatic diseases (8) . The presence of synovitis detected by MSUS is helpful in the diagnosis of undifferentiated arthritis (UA) and in inflammatory arthritis it is predictive of persistent disease, joint damage, and acute disease flare (9) . It has dramatically improved joint and tendon evaluation in rheumatoid arthritis (RA) and other inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%